2005
DOI: 10.1128/cdli.12.1.60-67.2005
|View full text |Cite
|
Sign up to set email alerts
|

Acute Inflammatory Response to Endotoxin in Mice and Humans

Abstract: Endotoxin injection has been widely used to study the acute inflammatory response. In this study, we directly compared the inflammatory responses to endotoxin in mice and humans. Escherichia coli type O113 endotoxin was prepared under identical conditions, verified to be of equal biological potency, and used for both mice and humans. The dose of endotoxin needed to induce an interleukin-6 (IL-6) concentration in plasma of ϳ1,000 pg/ml 2 h after injection was 2 ng/kg of body weight in humans and 500 ng/kg in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
275
3
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 359 publications
(301 citation statements)
references
References 39 publications
21
275
3
2
Order By: Relevance
“…This finding partially confirms a previous study performed by Copeland et al,9 which showed that, in blood, LPS triggers the secretion of several proinflammatory cytokines, such as tumor necrosis factor-a, IL-6 and IL-1, and induces transient lymphopenia, vasodilatation, impaired coagulation and fibrinolysis.…”
Section: Data Analysis and Statistical Evaluationsupporting
confidence: 92%
“…This finding partially confirms a previous study performed by Copeland et al,9 which showed that, in blood, LPS triggers the secretion of several proinflammatory cytokines, such as tumor necrosis factor-a, IL-6 and IL-1, and induces transient lymphopenia, vasodilatation, impaired coagulation and fibrinolysis.…”
Section: Data Analysis and Statistical Evaluationsupporting
confidence: 92%
“…First, the inflammatory response is dynamic, changing over time. Second, the inflammatory changes are not rapid spikes in plasma levels of cytokines such as observed after endotoxin exposure (46,47). These data indicate that measuring the inflammatory response every 24 h should be sufficient to profile the inflammatory status of the patient if a number of biomarkers are evaluated.…”
Section: Discussionmentioning
confidence: 93%
“…The Inflammation and Host Response to Injury, Large Scale Collaborative Research Program has completed multiple studies on the genomic responses to systemic inflammation in patients and human volunteers as well as murine models (14)(15)(16)(17)(18). These datasets include genome-wide expression analysis on white blood cells obtained from serial blood draws in 167 patients up to 28 d after severe blunt trauma (15), 244 patients up to 1 y after burn injury, and 4 healthy humans for 24 h after administration of low-dose bacterial endotoxin (14) and expression analysis on analogous samples from well-established mouse models of trauma, burns, and endotoxemia (16 treated and 16 controls per model) (16)(17)(18).…”
mentioning
confidence: 99%